Analysis on Electromagnetic Interference with Different Polarization of Electric Field - Yanpeng Sun; Lele Qu; Liwei Sun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A simplified modeling of shielding cavity with a wire penetrated was established, in order to study the coupling effects of electromagnetic pulse (EMP) with different incident angles when the shielding cavity has a penetrated wire. Finite-Difference Time-Domain (FDTD) was applied to analyze the rule of variation of coupling current magnetic field on the penetrated wire, with the variation of angles of incident wave. Further study shows that the electromagnetic energy coupled by penetrated wire when incident wave radiates aslant is more than the coupling energy when incident wave radiates the target vertically in the condition of vertical polarized direction of electric field, and less in the condition of horizontally polarized direction of electric field. And compared with the situation of horizontal polarized direction of electric field, more electromagnetic energy is coupled when the direction of electric field is vertically polarized. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5014